ANALISIS STRATEGI PENGEMBANGAN AGRIBISNIS SALAK DI KABUPATEN TAPANULI SELATAN - Utari Evy Cahyani (STIE DWI SAKTI BATURAJA, 2017)
The purpose of this study is to identify strengths, weaknesses, opportunities and threats and formulate strategies for agribusiness development in South Tapanuli Regency. This research use desciptive qualitative approach. The result of this research is strategies to develop salak agribusiness in South Tapanuli namely: (1) integrating cultivation, processing and marketing activities through agroedutourism, (2) cooperating with banking and financial institutions through Government facilities to increase capital, (3) increase farmer added value through cultivation processing training, and (4) rehabilitation of old barking plants